Helminths of the Marbled Goby (Pomatoschistus marmoratus), a Mediterranean Immigrant in the Black Sea Fauna - Kvach, Yu. (Вестник зоологии, 2010)
The marbled goby, Pomatoschistus marmoratus (Risso, 1810), the Mediterranean immigrant in the Black Sea fauna, was examined for the metazoan parasites. In total, 12 parasite species were found to occurre. The component community consists of 7 trematode species, two nematodes, two acanthocephalans, and one cestode species. Two parasite species (Aphalloides coelomicola and Dichelyne minutus) were represented by both adults and larvae, four parasite species were presented by adults (Asymphylodora pontica, Paratimonia gobii, Acanthocephaloides propinquus, and Telosentis exiguus), and six species were presented by larvae (Bothriocephalus gregarius, Cryptocotyle concavum, C. lingua, Pygidiopsis genata, Timoniella imbutiforme, and Contracaecum microcephalum). T. imbutiforme has the great tendency to join the infracommunity. The core of parasite fauna of the marbled goby consists of two specialists, A. coelomicola and P. gobii, which immigrated to the Black Sea together with their hosts. The co-immigration is a result of co-evolution of the parasites’ and host’s life cycles.